Advances in the research on myokine-driven regulation of bone metabolism - MingHong Shao; QiYang Wang; QiuNan Lv; YuQiong Zhang; GuoXi Gao; Sheng Lu (Heliyon, 2024)
The traditional view posits that bones and muscles interact primarily through mechanical coupling. However, recent studies have revealed that myokines, proteins secreted by skeletal muscle cells, play a crucial role in the regulation of bone metabolism. Myokines are widely involved in bone metabolism, influencing bone resorption and formation by interacting with factors related to bone cell secretion or influencing bone metabolic pathways. Here, we review the research progress on the myokine regulation of bone metabolism, discuss the mechanism of myokine regulation of bone metabolism, explore the pathophysiological relationship between sarcopenia and osteoporosis, and provide future perspectives on myokine research, with the aim of identify potential specific diagnostic markers and therapeutic entry points.